Biopolymer organization of the exine of Juniperus virginiana L., and Taxus baccata L. - Kedves Miklós (Plant cell biology and development, 1993)
Pollen grains of Juniperus virginiana L. and Taxus baccata L. were partially degraded with five different combination of solvents and oxidizing agents. These experiments were used following two basic methods: 1. Without heating before the solvent and oxidizing procedure. 2. The pollen grains were heated at 100 °C for one hour before the partial degradation. The solvated exines were fragmented with a magnetic stirrer in watered medium, for 30 minutes. With the transmission electron microscope several kinds of organization levels were observed, such as basic regular pentagonal polygons, PENROSE-like units, and their highly organized structures.